A Search to Integrate the Science Policy Works and “Turkish Science Policy 1983-2003” - İrfan ELMACI (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2017)
In Turkey, depending on the country's economic status and technological sophistication, science policy efforts were begun, science policy decisions were taken with 1960s and the issue was reflected to the official documents. However, an integrated program couldn’t have put into action for a long time to gather this fringe image showing science policy works. "Turkish Science Policy 1983- 2003”document of 1983 was an important step on the road to reach this purpose. But this document was not applied. In this article, aiming to reveal the reasons of this with history bases, the period from 1945 to 1983 is focused on. The subject is concluded by introducing "Turkish Science Policy 1983-2003”briefly and the results are obtained. The topic is enriched by comparing Turkey with some countries and Turkey's success was measured in this area.